Talqin Nikah Sebagai Budaya Untuk Menjaga Wewenang Wali Nasab Dalam Aqad Nikah (Jurnal Al-Fikrah, 2015)
Marriage contract is a special contract of the agreement such as the sale , pledge and others . Legalization of marriage in Islam is considered as a thing to be handled with care , because it will have implications for the law to various other matters arising from the marriage , such as nafaqah , heritage and also the sustainability of a happy home . One of the most important elements of the ceremony is the guardian of marriage . Only the female guardian who has the right to marry women who are in this authority. This was given by Islamic law to the guardian of marriage , because a woman can not marry himself . If a woman married herself , then her marriage is not legitimated. But in reality , guardians those have the right to marry sometimes are lose their right, because certain things , which requires that the rights of guardians move to another one in the hierarchy are the more distant ring thereof , when viewed from the aspect of virtue and validity.